ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH GURU PENGGERAK DALAM MENINGKATKAN MUTU PENDIDIKAN - Elmiya Sari; A. Faizin; Ahmad Thohirin; Suyitno Suyitno (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
Improving the quality of education is crucial for developing intelligent, competent, and character-based citizens who are ready to engage as individuals and members of society. The challenge in improving the quality of education is the disparity between urban and rural schools, with varying conditions, characteristics, and problems. A leadership style and POAC management strategy are needed for the principal and driving teacher as appropriate agents of change in managing school assets, including input, process, and product. This study examines in depth the implementation of the leadership style of the driving teacher principal in improving the quality of education. This study uses a qualitative descriptive method with a multi-case approach with important stages of data collection, namely interviews, observations, and documentation studies. The research subjects consisted of 2 principals, 8 teachers, 2 school committees, and 6 students. The main findings indicate that the implementation of transformational, servant, and democratic leadership styles can improve the quality of education at Muhammadiyah Bangil Creative Elementary School. Meanwhile, the implementation of situational, visionary leadership styles can improve the quality of education at Candi Binagun II Sukorejo Elementary School. Further findings indicate that the factors that influence the leadership style of the principal of the driving teacher are the values, roles, visions, and characters embedded in the principal of the driving teacher so that they can successfully implement the POAC management strategy by forming a school that fosters and improves the quality of education. It can be concluded that the values, roles, and visions of the driving teacher can shape the character of the leadership style in implementing the POAC management strategy. And transformational, visionary, servant, and democratic leadership styles can improve the quality of education in elementary schools with different school characteristics and cultures.  ABSTRAK Peningkatan mutu pendidikan sangat penting untuk membentuk warganegara yang cerdas, berkompetensi dan berkarakter yang siap terjun sebagai individu dan masyarakat. Tantangan yang dihadapi dalam meningkatkan mutu pendidikan yaitu adanya kesenjangan sekolah di perkotaan dan pedesaan dengan berbagai kondisi, karakter dan permasalahn yang dihadapi. Dibutuhkan gaya kepemimpinan dan strategi manajemen POAC kepala sekolah guru penggerak sebagai agen perubahan yang tepat dalam mengelola aset sekolah baik input, proses maupun produk. Penelitian ini mengkaji secara mendalam implementasi gaya kepemimpinan kepala sekolah guru penggerak dalam meningkatkan mutu pendidikan. Penelitian ini menggunakan metode kualitatif deskripsi dengan pendekatan multikasus dengan tahapan penting pengumpulan data yaitu wawancara, observasi, dan studi dokumentasi. Subjek penelitian terdiri dari 2 kepala sekolah, 8 guru, 2 komite sekolah dan 6 siswa. Temuan utama menunjukkan bahwa implementasi gaya kepemimpinan transformasional, servant dan demokratif dapat meningkatkan mutu pendidikan di SD Kreatif Muhammadiyah Bangil. Sedangkan implementasi gaya kepemimpinan situasional, visioner dapat meningkatkan mutu pendidikan di SDN Candi Binagun II Sukorejo. Temuan selanjutnya menunjukkan faktor -faktor yang memengaruhi gaya kepemimpinan kepala sekolah guru penggerak yaitu nilai, peran, visi dan karakter yang tertanam pada diri kepala sekolah guru penggerak  sehingga berhasil melaksanakan startegi manajemen POAC dengan membentuk sekolah yang menumbuhkan untuk meningkatkan mutu pendidikan. Dapat disimpulkan bahwa  nilai, peran, visi guru penggerak dapat membentuk karakter gaya kepemimpinan dalam melaksanakan strategi manajemen POAC. Dan gaya kepemimpinan transformasional, visioner, servant, demokratif dapat meningkatkan mutu pendidikan di sekolah dasar dengan karakteristik sekolah dan budaya yang berbeda.